Affluence, occupational safety and ergonomics: are they interdependent?. Issue 4 (1st October 2016) - Broszkiewicz, Roman
Abstract : The number of fatal occupational injuries (FOI), the number of scientific publications in ergonomics (SP) and the gross domestic product (GDP) of 30 countries were investigated for their mutual dependence. This article shows that, although the ratio of FOI/SP decreases exponentially with a linear increase in the GDP, GDP may be only one of the major influencing factors.